Short communication. Effect of housing system during the finishing period on growth performance and quality fat of Iberian pigs - Daza, A.; Esteban, M.; de Mercado, E.; Gomez, E. (Spanish Journal of Agricultural Research, 2010)
The objective of this experiment was to study the effect of housing system during the finishing period on growth performance and fat quality of Iberian pigs. Thirty barrows were used. During the finishing period, sixteen pigs were reared indoor and fourten pigs were reared outdoor in paddocks. The pigs housed in outdoor paddocks had higher ( p = 0.0001) feed average daily intake than those housed reared indoor and tended (p = 0.087) to show a worse feed efficiency. The C12:0 and C20:0 proportions in subcutaneous backfat from the pigs housed in outdoor paddocks were lower than those from the pigs housed reared indoor, whereas C17:0, C17:1 and C20:1 proportions tended (p = 0.09) to be lower. However, C18:1 n-9 and C18:3 n-3 proportions and C18:1 n-9/C18:0 ratio tended (p = 0.10) to be higher in the outdoor pigs than in the indoor pigs. In intramuscular fat from Longissimus dorsi muscle the C18:3 n-3 proportion tended (p = 0.07) to be higher in outdoor pigs than in indoor pigs. It is concluded that the finishing period of Iberian pigs in outdoor paddocks has a negative effect on feed conversion ratio but may improve the fat quality.